Nanomaterial‐mediated platinum drug‐based combinatorial cancer therapy. Issue 1 (16th November 2020) - Deng, Zhiqin; Wang, Na; Ai, Fujin; Wang, Zhigang; Zhu, Guangyu
Abstract: Platinum (Pt)‐based drugs represent some of the most successful anticancer agents in the clinic, and they have greatly accelerated the development of cancer chemotherapy. The therapeutic efficacy of platinum drugs, however, is limited by their various side effects and the development of drug resistance by cancer cells. To address these limitations, platinum drugs are combined with other therapeutic agents as a first‐line therapy for several types of cancer, and these treatments have achieved inspiring therapeutic outcomes. In some cases, however, such combinatorial treatments are inefficacious, due to the severe side effects, the short circulation half‐lives, and the different pharmacokinetic properties of the combined drugs. The rapid development of nanotechnology brings opportunities to surmount these limitations. Coloading platinum drugs and other anticancer agents into nanoparticles not only increases their synergistic efficacy but also improves their pharmacokinetic properties, tumor‐targeting efficiency, and other attributes that are favorable for cancer treatment. In this review, we summarize the recent developments in the application of nanotechnology for combinatorial therapy involving platinum drugs, with a focus on the design, anticancer efficacy, and other advantages of nanoparticles combining platinum drugs and other bioactive moieties. We also discuss the current challenges of these approaches and the prospects for their further development. Our summary and outlook will assist researchers to generate new ideas for the development of highly potent anticancer nanomedicine containing Pt‐based drugs. Abstract : Nanomaterial‐based combination of platinum drugs with chemotherapy, photodynamic therapy, photothermal therapy, or immunotherapy has demonstrated improved anticancer efficacy over single platinum therapy. This review summarizes recent progress in this emerging field with a focus on the design, anticancer efficacy, and other advantages of these combinatorial therapies.